Обобщенная структура жизненного цикла машиностроительного производства и его изделий - Тимофеев, Юрий Викторович; Фадеев, Валерий Андреевич; Степанов, Михаил Сергеевич; Назаренко, Сергей Александрович (НТУ "ХПИ", 2009)
Theoretical fundamentals of an integrated Continuous Acquisition and Life-cycle Support system structure are its subsystems are given. Conditions and ways to increase their elements Product Lifecycle Management efficiency are described. Structures optimization methods set application are described.
Keywords: жизненный цикл изделия; машиностроительное производство; интенсификация производства; параметры точности изделия